Restore yourself with tai chi becoming one with nature - Lee, Martin 1936-; Lee, Emily; TC Master; Lee, Melinda; Lee, Joyce (Sterling Publishing Co., Inc., 2002)
It is many forms of exercise in one--a stretching routine, deep-breathing program, martial art, and dance wrapped up in a single workout that anyone of any age can do. Even more, tai chi enhances both spirit and body, being almost a prayer in movement. And, with this extraordinary self-healing method, developed by a renowned tai chi master, it also offers relief for stress, muscular ailments, chronic headaches, and a variety of other modern office and sports-related complaints. The central focus of this "physical philosophy" is on the flow of energy and becoming one with nature; and its benefits include inner happiness, self-control, self-realization, and all-around wellness. Each of these goals receives in-depth attention, complete with 64 tai chi forms, all thoroughly illustrated with photographs and diagrams. Here is a valuable health, exercise, and meditation program that combines age-old insights with advanced scientific knowledge and important original discoveries.